Identification of a novel C16orf57 mutation in Athabaskan patients with Poikiloderma with Neutropenia. - IRVINE, ALAN (My University, 2011)
Poikiloderma with Neutropenia (PN), Clericuzio-Type (OMIM #604173) is characterized by poikiloderma, chronic neutropenia, recurrent sinopulmonary infections, bronchiectasis, and nail dystrophy. First described by Clericuzio in 1991 in 14 patients of Navajo descent, it has since also been described in non-Navajo patients. C16orf57 has recently been identified as a causative gene in PN. The purpose of our study was to describe a spectrum of C16orf57 mutations in a cohort of PN patients including five patients of Athabaskan (Navajo and Apache) ancestry. Eleven patients from eight kindreds were enrolled in an IRB-approved study at Baylor College of Medicine. Five patients were of Athabaskan ancestry. PCR amplification and sequencing of the entire coding region of the C16orf57 gene was performed on genomic DNA. We identified biallelic C16orf57 mutations in all 11 PN patients in our cohort. The seven new deleterious mutations consisted of deletion (2), nonsense (3), and splice site (2) mutations. The patients of Athabaskan ancestry all had a common deletion mutation (c.496delA) which was not found in the six non-Athabaskan patients. Mutations in the C16orf57 gene have been identified thus far in all patients studied with a clinical diagnosis of PN. We have identified seven new mutations in C16orf57 in PN patients. One of these is present in all patients of Athabaskan descent, suggesting that c.496delA represents the PN-causative mutation in this subpopulation.
PUBLISHED
Keywords: Poikiloderma with Neutropenia (PN); Immunology, Inflammation & Infection